Opposition political parties’ coalition in Zimbabwe: Challenges and possibilities - Mungwari Teddy; Ephraim Vhutuza (Academic Journals, 2023)
This paper discusses the prevalent view among ordinary Zimbabweans that only a grand coalition among select opposition political parties could potentially unseat the ruling party, Zimbabwe African National Union Patriotic Front (ZANU PF) from power in the upcoming 2018 general elections. The paper argues that the prospects for such a grand coalition are only possible if select parties coalesce around the major opposition party, the Movement for Democratic Change-Tsvangirai (MDC-T). This article takes this argument as the starting point for a discussion of the role and character of opposition political parties and party systems in Zimbabwe and further considers aspects of the performance of individual parties to date and the extent to which they fall short of people’s expectations, what in this paper constitutes possibilities and challenges in forging a formidable grand coalition given the magnitude of mistrust within and among them. The state-controlled daily, The Herald was examined to ascertain how it framed the coalition of opposition parties in Zimbabwe. Therefore, secondary data analysis and observation through the lenses of a qualitative approach, of the unfolding political environment in Zimbabwe was done. The Herald which is supposed to be a public newspaper is allegedly a mouthpiece of the ruling party ZANU PF. It was concluded that The Herald’s representation of the coalition was propagandistic. It was also concluded that despite personality clashes, mistrust, infiltration, bloated ambitions among leaders and party egos, a grand coalition is possible and that this could possibly fare better than if individual parties contest ZANU PF individually